A novel combined treatment process of hybrid biosorbent nanofiltration for effective PbII removal from wastewater - Hanif, Asma; Ali, Shaukat; Hanif, Muhammad Asif; Rashid, Umer; Bhatti, Haq Nawaz; Asghar, Muhammad; Alsalme, Ali; Giannakoudakis, Dimitrios A. (Multidisciplinary Digital Publishing Institute, 2021)
The untreated effluents discharged by different industries, such as metallurgy, fertilizers, pesticide, leather, mining, electroplating, surface finishing, aerospace, and electroplating, have increased the risk of the contamination of bodies of water by heavy metals. Herein, hybrid biosorbent–nanofiltration processes for Pb(II) removal from wastewater was studied. The hybrid biosorbent was prepared from date seed waste and Ganoderma lucidum. Hybrid biosorbent characterization was performed by SEM and FTIR. SEM micrographs showed that the HB surface is irregular. For the adsorption studies, various sorption parameters were optimized. The maximum biosorption capacity of immobilized heat-inactivated hybrid biosorbent was 365.9 mg/g, with the Langmuir isotherm model to present the best fit. Desorption experiments were conducted for regenerating immobilized heat-inactivated hybrid biosorbent for three consecutive cycles using different desorption agents, with acetic acid to be the optimum. Going a step further, nanofiltration was also applied as a post-treatment process to elevate the remediation effectiveness for wastewater of high Pb(II) initial concentrations. The reasonably low cost and high removal of Pb(II) make hybrid biosorbent–nanofiltration processes a prosperous and potentially attractive hybrid approach against heavy-metal-polluted wastewater.